ANALISIS HARGA JUAL MENGGUNAKAN METODE COST PLUS PRICING DENGAN PENDEKATAN FULL COSTING - Nurdiwaty, Diah; Widiawati, Hestin Sri (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
Every company definitely wants its products to compete with other similar companies in the market. One of the determining factors is the selling price. Determining the selling price by calculating the cost of production using the right method will produce maximum profits. One method that can be used is cost plus pricing. The aim of this research is to analyze the calculation of the cost of production using the cost plus pricing method to determine the selling price. with a full costing approach at UD Mekar Jaya Kediri. The analysis used in this research is quantitative descriptive, where the calculations used by UD Mekar Jaya will be compared with the theory used in determining the selling price. The research uses data in the form of production cost reports for 2023. The conclusions of the research results are 1) UD Mekar Jaya Kediri in determining selling prices only uses estimates so that determining the cost of production is less precise and very simple 2) calculation of the cost of production is based on a full costing and price approach. selling based on the cost plus pricing method produces higher value 3) there is a difference in value because there are several cost elements that are not included including fuel costs, equipment maintenance costs, depreciation costs 4) the full costing method can be used as a cost control tool.